2021
DOI: 10.1371/journal.pone.0261984
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum expression of p53 and association of TP53 codon 72 polymorphisms with risk of cervical cancer in Bangladeshi women

Abstract: Differential expression of p53 has been reported in cervical cancer, primarily in tumor tissue biopsies. In this study, we examined the association of TP53 codon 47 and codon 72 polymorphisms and serum level expression of p53 in cervical cancer patients (n = 129) and healthy controls (n = 122). We found elevated levels of serum p53 protein levels in cervical cancer patients (p = 0.0442) compared to healthy controls. Moreover, we found higher levels of serum p53 in patients with grade-III tumor (p = 0.001) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…We also found a significant difference ( p = 0.013) regarding the use of contraceptives as women who used intrauterine device, cervical cap, barrier, and female condom were more prone to the risk of cancer. This is similar to our findings with a different cohort of cervical cancer patients, where we found that similar contraceptives increase the risk of cervical cancer in Bangladeshi women 40 . However, no statistically significant difference was observed for age, menopausal status, dwelling status, parity, postmenopausal status, number of children, and family history of cancer.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We also found a significant difference ( p = 0.013) regarding the use of contraceptives as women who used intrauterine device, cervical cap, barrier, and female condom were more prone to the risk of cancer. This is similar to our findings with a different cohort of cervical cancer patients, where we found that similar contraceptives increase the risk of cervical cancer in Bangladeshi women 40 . However, no statistically significant difference was observed for age, menopausal status, dwelling status, parity, postmenopausal status, number of children, and family history of cancer.…”
Section: Resultssupporting
confidence: 91%
“…Our study demonstrated that women who used intrauterine devices and barrier methods (cervical cap, diaphragm, female condom) of contraception had a significantly higher risk of developing cervical cancer ( p = 0.013). This finding is similar to a previous study of ours with a different cohort of cervical cancer patients 40 . Previous studies reported a high prevalence of cancer among workers in the synthetic rubber industry suggesting that the soft silicone and synthetic latex used in these products may have some carcinogenic properties, contributing to cervical cancer 44 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The p53 gene has polymorphism and contains coding and non-coding regions. Most of these polymorphisms contain single nucleotide polymorphisms (SNPs), and these polymorphisms are located on code 47 and code 72, and this code is functionally important because it is associated with coding for the arginine and proline alleles, which are associated with the occurrence of many types of cancer, including prostate cancer (Mostaid et al, 2021), my study (Doosti and Dehkordi, 2011;Mittal et al, 2011) indicated a highly significant association of genotypes (Homozygotes proline & Homozygote arginine) for the polymorphism of the p53Codon 72 gene with prostate cancer, while no significant relationship of the (Heterozygotes proline-arginine) genotype with the disease has been proven (Huang et al, 2004;Rogler et al, 2011) which did not prove a significant association between any of the genotypes of the Codon 72 p53 gene with prostate cancer, and justifies the reason for the emergence and disappearance of genotypes and its association or not with prostate cancer in the world to the variation of gene expression according to Environment and Ethnicity ) Hong et al, 2019).…”
Section: Molecular Diagnosis Of the Polymorphism In P53codon 72 Gene ...mentioning
confidence: 99%